2016
DOI: 10.1016/j.nicl.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Low putamen activity associated with poor reward sensitivity in childhood chronic fatigue syndrome

Abstract: Motivational signals influence a wide variety of cognitive processes and components of behavioral performance. Cognitive dysfunction in patients with childhood chronic fatigue syndrome (CCFS) may be closely associated with a low motivation to learn induced by impaired neural reward processing. However, the extent to which reward processing is impaired in CCFS patients is unclear. The aim of the present functional magnetic resonance imaging (fMRI) study was to determine whether brain activity in regions related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Therefore, we surmised that the finding of the putamen, whose rGMD was linked to dispositional optimism, may reflect the motivational characteristics of dispositional optimism. More concretely, the putamen has been demonstrated to be involved in several motivation‐related processes, for example, history‐based reward value encoding, action selection, and cue‐action‐dependent reward prediction (Elliott, Newman, Longe, & Deakin, ; Haruno & Kawato, ; Hori, Minamimoto, & Kimura, ; Kunimatsu, Maeda, & Hikosaka, ; Mizuno et al, ; Muranishi et al, ; Pessiglione, Seymour, Flandin, Dolan, & Frith, ; Schultz, ). For example, several studies have shown that the putamen was closely associated with reward value encoding and action selection based on past experience (Kunimatsu et al, ; Muranishi et al, ), and that these processes, i.e., history‐based reward value updating and action selection, were impaired if the neural activity in the putamen was blocked (Muranishi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we surmised that the finding of the putamen, whose rGMD was linked to dispositional optimism, may reflect the motivational characteristics of dispositional optimism. More concretely, the putamen has been demonstrated to be involved in several motivation‐related processes, for example, history‐based reward value encoding, action selection, and cue‐action‐dependent reward prediction (Elliott, Newman, Longe, & Deakin, ; Haruno & Kawato, ; Hori, Minamimoto, & Kimura, ; Kunimatsu, Maeda, & Hikosaka, ; Mizuno et al, ; Muranishi et al, ; Pessiglione, Seymour, Flandin, Dolan, & Frith, ; Schultz, ). For example, several studies have shown that the putamen was closely associated with reward value encoding and action selection based on past experience (Kunimatsu et al, ; Muranishi et al, ), and that these processes, i.e., history‐based reward value updating and action selection, were impaired if the neural activity in the putamen was blocked (Muranishi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More concretely, the putamen has been demonstrated to be involved in several motivation-related processes, for example, history-based reward value encoding, action selection, and cue-action-dependent reward prediction (Elliott, Newman, Longe, & Deakin, 2004;Haruno & Kawato, 2006;Hori, Minamimoto, & Kimura, 2009;Kunimatsu, Maeda, & Hikosaka, 2019;Mizuno et al, 2016;Muranishi et al, 2011;Pessiglione, Seymour, Flandin, Dolan, & Frith, 2006;Schultz, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that dopaminergic activation may be related to the yoga-induced increase in vigor. Previous studies have demonstrated that patients with CFS exhibited reduced neural activation of the caudate nucleus in response to a reward task [ 16 ] and of the putamen [ 17 ], which may be due, in part, to dopaminergic dysfunction [ 16 , 17 ]. Thus, reduced dopamine activity may contribute to symptoms of low energy in patients with CFS and dopaminergic activation may have a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctions of the immune system include increased blood levels of multiple cytokines, including transforming growth factor (TGF)-β1 and several proinflammatory cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-6, and interferon (IFN)-γ [ 12 15 ]. Dysfunctions of the CNS include hypoactivity of the dopaminergic nervous system to reward stimuli [ 16 , 17 ]. Other dysfunctions in patients with CFS include lower blood levels of acylcarnitine than in healthy subjects [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in motivational neural circuitry were associated with increases in mental and general fatigue and reductions in physical activity in adult CFS [ 81 ]. Previous fMRI studies with children and adolescents with CFS found changes in activities of the prefrontal and parietal regions during attentional control [ 82 ] and decreases in striatal activity involved in reward sensitivity and motivation [ 83 ].…”
Section: Discussionmentioning
confidence: 99%